Correlation analysis of cytokine levels and Th2, Th17, and Treg cells in allergic rhinitis: Cytokine levels in allergic rhinitis - Yao, Mei; Liu, Luoguo; Wen, Jingda; Zhang, Weishi (Journal of Medical Biochemistry, 2025)
Objective: To explore the roles of Th2, Th17, and regulatory T (Treg) cells and their related cytokines and transcriptional genes in the pathogenesis of allergic rhinitis (AR). Methods: A total of 200 patients who were diagnosed with AR in our hospital from October 2023 to October 2024 were randomly selected as the AR group. According to the visual analog scale (VAS) score, the AR group was further divided into a mild allergic rhinitis group (MAR group) and a severe allergic rhinitis group (SAR group). Moreover, 50 healthy people who underwent physical examinations at the Physical Examination Center of Ordos Central Hospital composed the healthy control group (HC group). Blood from peripheral veins was drawn on the day of registration. The Th17/Treg ratio and the proportions of helper T 2 (Th2), helper T 17 (Th17), and Using flow cytometry, the number of regulatory T (Treg) cells among the peripheral blood’s CD4+T cells was determined. The enzyme-linked immunosorbent assay (ELISA) was used to determine the levels of interleukin-4 (IL-4), interleukin-5 (IL-5), interleukin-10 (IL-10), and interleukin-17 (IL-17) in the patients’ serum. The genes GATA-3 mRNA, RORyt-mRNA, and FOXP3-mRNA’s relative expression levels were assessed using real-time fluorescence quantitative RT-PCR of peripheral blood mononuclear cells. Results: The peripheral blood of AR patients had larger Th2/Th17/Treg cell proportions and a higher Th17/Treg ratio. The AR group presented greater differences (P<0.05), and both were positively connected with the disease severity, with the SAR group showing larger differences than the MAR group (P<0.05). AR patients had higher peripheral blood levels of IL-4, IL-5, IL-17, and IL-10. The severity of the disease was positively connected with the differences from the AR group (P<0.05) and the SAR group (P<0.05) compared to the HC group and the MAR group, respectively. Patients with AR had higher relative expression levels of the transcription genes FoxP3, RORyt, and GATA-3 in their peripheral blood mononuclear cells. The AR group showed more differences than the HC group (P<0.05), while the SAR group showed more differences than the MAR group (P<0.05). These differences were all positively connected with the illness severity. The relative expression level of GATA-3 mRNA and the serum levels of IL-4 and IL-5 were positively connected with Th2 cells. Th17 cells showed a favorable correlation with both the relative expression level of RORyt-mRNA and the content of serum L-17. Treg cells showed a favorable correlation with both the relative expression level of FoxP3 mRNA and the serum IL-10 levels. Binary logistic regression analysis revealed that an increase in the proportion of Th2 and Th17 cells; a continuous increase in the Th17/Treg ratio; an increase in the concentrations of IL-4, L-5, and IL-17; and an increase in the relative expression levels of GATa-3 mRNA and RORyt-mRNA transcriptional genes were risk factors for SAR. Conclusion: A persistently elevated Th17/Treg ratio in AR patients indicates progressive exacerbation of AR. The relative expression levels of the transcription genes GATA-3, RORyt-mRNA, and FoxP3-mRNA in peripheral blood mononuclear cells lead to increases in the proportions of Th2, Th17, and Treg cells.